Albania : Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report ;, 2002)
This paper evaluates Albania's Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF). Sound financial policies under the previous PRGF-supported program helped stabilize the economy and restore high growth, but poverty remains widespread. The authorities' medium-term strategy aims to promote inclusive growth, as the country continues to be plagued by poverty. The proposed PRGF arrangement is justified by the authorities' commendable performance under the previous PRGF arrangement and their strong measures for addressing the remaining policy challenges.